Effect of Fin and Insert on the Performance Characteristics of Close Loop Pulsating Heat Pipe (CLPHP). (2015) - Rahman, M. Lutfor; Nawrin, Sumaiya; Sultan, Rasel A.; Mir, Fariha; Ali, Mohammad
Abstract: The pulsating heat pipe, a serpentine tube of capillary dimension with many turns, has great impact on today's successful thermal management. It is an ascending technology to satisfy present requirement of increasing thermal performance. Focusing on this, an experiment has been done on the close loop pulsating heat pipes (CLPHP) to observe their performance characteristics by using two working fluids with varying inclination angles of 0̊ (vertical), 30̊ and 45̊. The experiment is performed on 2.5 mm inner diameter and 3 mm outer diameter CLPHP with an insert of copper wire of 1 mm diameter and fins are added on the condensation section where the evaporation section is 50 mm, adiabatic section is 120 mm and condensation section is 80 mm. This investigation is done using ethanol and methanol with 50% filling ratio in CLPHP with 8 loops. Methanol shows better performance at 45̊inclination than ethanol due to their physiochemical properties at different conditions. In this experiment the effects on the performance of using fins with insert and the variation of inclination angles are investigated. The results show the better performance characteristics and enhancement of heat transfer in the present experimental set-up because of using fin and insert.